Hybridization alters growth and migratory life‐history expression of native trout. (18th December 2020) - Strait, Jeffrey T.; Eby, Lisa A.; Kovach, Ryan P.; Muhlfeld, Clint C.; Boyer, Matthew C.; Amish, Stephen J.; Smith, Seth; Lowe, Winsor H.; Luikart, Gordon
Abstract: Human‐mediated hybridization threatens many native species, but the effects of introgressive hybridization on life‐history expression are rarely quantified, especially in vertebrates. We quantified the effects of non‐native rainbow trout admixture on important life‐history traits including growth and partial migration behavior in three populations of westslope cutthroat trout over five years. Rainbow trout admixture was associated with increased summer growth rates in all populations and decreased spring growth rates in two populations with cooler spring temperatures. These results indicate that non‐native admixture may increase growth under warmer conditions, but cutthroat trout have higher growth rates during cooler periods. Non‐native admixture consistently increased expression of migratory behavior, suggesting that there is a genomic basis for life‐history differences between these species. Our results show that effects of interspecific hybridization on fitness traits can be the product of genotype‐by‐environment interactions even when there are minor differences in environmental optima between hybridizing species. These results also indicate that while environmentally mediated traits like growth may play a role in population‐level consequences of admixture, strong genetic influences on migratory life‐history differences between these species likely explains the continued spread of non‐native hybridization at the landscape‐level, despite selection against hybrids at the population‐level.